2018
DOI: 10.1056/nejmoa1713231
|View full text |Cite
|
Sign up to set email alerts
|

Change in Overweight from Childhood to Early Adulthood and Risk of Type 2 Diabetes

Abstract: Childhood overweight at 7 years of age was associated with increased risks of adult type 2 diabetes only if it continued until puberty or later ages. (Funded by the European Union.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
232
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(255 citation statements)
references
References 30 publications
14
232
2
7
Order By: Relevance
“…Modelling of growth trajectories from childhood has suggested that the majority of children in the United States (57%) will be obese by the age of 35 (Ward et al, ), with half of this projection being established in childhood. However, a recent longitudinal analysis of over 62,000 men living in Denmark suggested that the adverse long‐term health effects of childhood overweight can be reversed if weight is normalised prior to puberty (Bjerregaard et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Modelling of growth trajectories from childhood has suggested that the majority of children in the United States (57%) will be obese by the age of 35 (Ward et al, ), with half of this projection being established in childhood. However, a recent longitudinal analysis of over 62,000 men living in Denmark suggested that the adverse long‐term health effects of childhood overweight can be reversed if weight is normalised prior to puberty (Bjerregaard et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, nearly 23% of children throughout the world are either overweight or obese . Childhood obesity is the strongest predictor of adult obesity which accelerates onset of diseases including cardiovascular disorders, diabetes, and multiple types of cancer .…”
Section: Introductionmentioning
confidence: 99%
“…At present, nearly 23% of children throughout the world are either overweight or obese . Childhood obesity is the strongest predictor of adult obesity which accelerates onset of diseases including cardiovascular disorders, diabetes, and multiple types of cancer . In developed countries where nutrition is bountiful and death rates from infectious diseases are low, an increase in weight in childhood provides only a few benefits in protecting against infection .…”
Section: Introductionmentioning
confidence: 99%
“…During puberty, body size and fat distribution change dramatically. It is shown that overweight, especially during puberty, modifies the risk of type 2 diabetes in adulthood, while normalization of BMI before puberty may reduce this risk …”
Section: Introductionmentioning
confidence: 99%